Impact of Corporate Social Responsibility on Social Economic Changes in Belibak Village Community: Dampak Corporate Social Responsibility Terhadap Perubahan Sosial Ekonomi Masyarakat Desa Belibak - Asdaq, Teguh Miftah (Progress In Social Development, 2022)
ABSTRACT:The activities of a company can have a big impact on the community around its operating area, changes in socio-economic patterns are one of the impacts that are quite real on the community, these changes can lead to good or bad. The Corporate Social Responsibility (CSR) activity in Belibak Village is one clear evidence of a change in the socio-economic pattern of the community around the corporate area. This study aims to describe how CSR activities have a direct impact on people's lives and describe how these activities began to change the way of life of the Belibak Village community. This research was arranged in a qualitative method with an ethnographic field methodology, data collection was carried out directly for 2 months (1 September – 1 November 2021) in Belibak Village, Kec. Palmatak, Anambas Islands. The result in the case of Belibak Village is that this CSR activity has changed the socio-economic pattern of the community affected by the sustainable development program. ABSTRAK:Aktivitas suatu perusahaan bisa membawa dampak besar terhadap masyarakat disekitar wilayah operasinya, perubahan pola sosial ekonomi merupakan salah satu dampak yang cukup nyata terhadap masyarakat, perubahan ini bisa mengarah baik ataupun buruk. Aktivitas Corporate Social Responsibility (CSR) di Desa Belibak salah satu bukti nyata terjadinya perubahan pada pola sosial ekonomi masyarakat sekitar kawasan korporasi. Penelitian ini bertujuan untuk menggambarkan bagaimana aktivitas CSR berdampak langsung pada kehidupan masyarakat dan mendeskripsikan bagaimana aktivitas ini mulai mengubah tatanan hidup masyarakat Desa Belibak. Penelitian ini disusun dalam metode kualitatif dengan metodologis lapangan Etnografi, pengambilan data dilakukan langsung selama 2 bulan (1 September – 1 November 2021) di Desa Belibak, Kec. Palmatak, Kepulauan Anambas. Hasilnya pada kasus Desa Belibak aktivitas CSR ini telah mengubah pola sosial ekonomi masyarakat yang terdampak program pembangunan berkelanjutan.